Clinical Analysis: Aqueous-Deficient and Meibomian Gland Dysfunction in Patients With Primary Sjogren's Syndrome - Wang, Yi; Qin, Qiyu; Liu, Bo; Fu, Yana; Lin, Lin; Huang, Xiaodan; Jin, Xiuming (Frontiers in Medicine, 2019)
Objective: To examine the time course of aqueous-deficient and meibomian gland dysfunction (MGD) in patients with primary Sjogren’s Syndrome (pSS). Methods: This prospective study was conducted on pSS female patients in the Department of Rheumatism of the Second Affiliated Hospital, School of Medicine, Zhejiang University. The age-matched MGD female patients without pSS (non-SS-MGD) were recruited as MGD controls from the Eye Center of the Second Affiliated Hospital, School of Medicine, Zhejiang University. After providing written informed consent, the patients underwent an eye examination and completed an Ocular Surface Disease Index questionnaire that assessed the symptoms of dry eye disease. The subjects were evaluated using Schirmer I test (SIt), tear meniscus height (TMH), noninvasive keratographic break-up time (NIKBUT), corneal fluorescein staining (CFS), and meibomian gland evaluation (meibomian gland infrared, lid margin score, expressible meibomian glands number and the secretions quality). The patients were divided into two groups: early stage (≤3 years) and late stage (>3 years) according to their medical history of dry eye. The data were analyzed using SPSS 20.0. Results: There were 49 pSS and 52 non-SS-MGD female patients enrolled in this study from 1 January 2018 to 30 December 2018. There were no differences in age (49.38 ± 10.32 and 48.69 ± 13.57 years) and dry eye medical history (48.44 ± 40.16 and 47.79 ± 37.85 months) between the two groups. When the medical history was ≤3 years, the average SIt and TMH of the pSS patients were significantly smaller than those of the patients with MGD. However, the signs related to the MGD did not show a significant difference between the two groups. When the medical history was >3 years, both the SIt and TMH and the signs related to MGD in pSS group were significantly more severe than the MGD group. Conclusions: Our results demonstrated that 3 years may be an important time node for the dry eye development in pSS patients, before this, the lacrimal glands received a greater influence, and then the meibomian glands began to be greatly affected.